LARA, G. M. P; MACHADO, I. D; EMEDIATO, W. (org). Análises do discurso hoje, vol. 2. Rio de Janeiro: Nova Fronteira , 2008, 318 páginas. (Cadernos de Linguagem e Sociedade, 2010)
LARA, G. M. P; MACHADO, I. D; EMEDIATO, W. (org). Análises do discurso hoje, vol. 2. Rio de Janeiro: Nova Fronteira , 2008, 318 páginas.